A Unified Linear Free Energy Relationship for Abiotic Reduction Rate of Nitroaromatics and Hydroquinones Using Quantum Chemically Estimated Energies. (19th October 2020) - Hickey, Kevin P.; Di Toro, Dominic M.; Allen, Herbert E.; Carbonaro, Richard F.; Chiu, Pei C.
Abstract: Determining the fate of nitroaromatic compounds (NACs) in the environment requires the use of predictive models for compounds and conditions for which experimental data are insufficient. Previous studies have developed linear free energy relationships (LFERs) that relate the thermodynamic energy of NAC reduction to its corresponding rate constant. We present a comprehensive LFER that incorporates both the reduction and oxidation half‐reactions through quantum chemically calculated energies. Environ Toxicol Chem 2020;39:2389–2395. © 2020 SETAC Abstract : Reaction kinetics as a function of nitroaromatic compounds (NACs) reduction and hydroquinone oxidation energies calculated via a hydrogen atom transfer mechanism with density functional theory for 7 NACs and 6 hydroquinones.